Trends in alcohol consumption during COVID-19 lockdowns: systematic review. (20th October 2021) - Acuti Martellucci, C; Martellucci, M; Flacco, ME; Manzoli, L
Abstract: Background: The spread of SARS-CoV-2 required virtually all governments to employ non-pharmaceutical infection containment measures such as quarantine and generalised lockdowns. Several authors raised warnings about potential negative changes in alcohol-related behaviours due to the lockdowns. The objective of the present systematic review was to summarise available evidence on trends of alcohol consumption temporally associated with COVID-19 lockdowns. Methods: We performed a systematic review in PubMed, Scopus, Web of Science and EMBASE, using the search terms 'coronavirus', with either 'alcohol drinking', 'alcoholism', 'alcoholic beverages', and 'alcohol intoxication'. Studies were included if they evaluated the change in alcohol consumption prevalence or frequency both before and during the lockdowns, or if they assessed changes in alcohol use retrospectively. The outcomes were changes in prevalence of alcohol consumption, or in its frequency. Results: A total of 128 records were retrieved, and 24 studies met eligibility criteria. Most samples were drawn from either the general population (e.g. social media users), university students, or regular drinkers. The outcomes measurements varied widely, and multiple scales were also used for the assessment of harmful alcohol use. The majority of the studies found that alcohol consumption prevalence increased during lockdowns (e.g. +25.7% in UK). Also, increased frequencies were reported by 14.0% in Poland and 32.1% in China. Finally, one study from Australia observed no overall changes, while one from Cyprus reported decreased alcohol consumption frequency. Conclusions: Understanding the impact of lockdowns on alcohol consumption is essential for countering possible increases in harmful use, and a consensus should be reached for performing standardised and comparable assessments. Key messages: Alcohol consumption increased in many countries during the COVID-19 lockdowns, with local variations. Assessments used a great variety of outcomes, hindering a comprehensive assessment of this phenomena.